Genetic Resources of Shade Tolerant Forage Crops - Purwantari, Nurhayati Diah (Indonesian Animal Sciences Society, 2016)
Forage crops are planted mostly in marginal land or integrated with other crops. Estate crops land is one of the alternative areas for forage crops plantation. Shortage of forage crops development under crop plantation is caused by limited light intensity, due to crop shading. Selecting forage crops adapted to estate crops plantation is crusial to achieve its high production and quality. Several grasses and legumes have been identified as forage crops that tolerant to shading of less than 40%, 40-60% and more than 60% light intensity. Some of them have been applied in the area of oil palm plantation to support the acceleration of livestock population. Â